Co-evolution of matrisome and adaptive adhesion dynamics drives ovarian cancer chemoresistance - Elina A. Pietilä (Nature Portfolio, 2021)
Platinum chemotherapy is standard of care in ovarian cancers but treatment resistance commonly develops. Here, the authors show that the extracellular microenvironment is modulated following chemotherapy and the changes in matrix proteins and stiffness alter the cell death response of tumour cells.